2007
DOI: 10.2500/ajr.2007.21.3060
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti-IgE Immunoglobulin Therapy in Nasal Polyposis: A Pilot Study

Abstract: This pilot study provides new evidence establishing that (1) endoscopic NP severity directly correlates to total serum IgE levels and (2) inclusion of anti-IgE therapy in the postpolypectomy management of atopic asthmatic individuals may reduce the severity of NP recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 9 publications
3
55
0
5
Order By: Relevance
“…Previous studies suggest that this therapy is efficacious in CRS management with regard to objective measures of disease severity, such as the burden of polyposis assessed endoscopically and/or radiologically. [7][8][9] Some have also shown reduction in symptoms of both CRS and comorbid asthma. 9 The goal of the present study was to examine the impact of omalizumab therapy upon control of comorbid CRS in asthmatic patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies suggest that this therapy is efficacious in CRS management with regard to objective measures of disease severity, such as the burden of polyposis assessed endoscopically and/or radiologically. [7][8][9] Some have also shown reduction in symptoms of both CRS and comorbid asthma. 9 The goal of the present study was to examine the impact of omalizumab therapy upon control of comorbid CRS in asthmatic patients.…”
Section: Discussionmentioning
confidence: 96%
“…[7][8][9] Some have also shown reduction in symptoms of both CRS and comorbid asthma. 9 The goal of the present study was to examine the impact of omalizumab therapy upon control of comorbid CRS in asthmatic patients. Specifically, we hypothesized that the average number of antibiotic courses and the mean cumulative oral steroid dosage administered for CRS would decrease significantly after initiating omalizumab therapy.…”
Section: Discussionmentioning
confidence: 96%
“…The first report for the potential efficacy of this agent in patients with CRSwNP was published by Penn et al (24) in 2007. In this pilot study, 4 patients with nasal polyposis and comorbid asthma reported a statistically significant difference between the pre and post omalizumab treatment endoscopic scores, which were not combined with statistically relevant differences in their CT scores.…”
Section: Discussionmentioning
confidence: 99%
“…Omalizumab, a recombinant human anti-immunoglobulin E (IgE) antibody, is indicated for the treatment of moderate to severe persistent asthma and chronic urticaria. Capitalizing upon evidence showing localized IgE production in sinonasal mucosa, 7 and prior demonstration of improvement in objective CRS parameters with omalizumab, [7][8][9] Chandra et al 10 studied a cohort of 25 CRS patients being treated with omalizumab for asthma. These authors note a 37% decrease in mean antibiotic prescriptions per month in CRS patients, and a subset of CRS patients also demonstrated notable decreases in steroid dependence.…”
mentioning
confidence: 98%